Pengaruh Pengawasan, Disiplin Kerja Dan Motivasi Terhadap Kinerja Karyawan Pada PT Microcast Technology Indonesia - Haria, Tomi; Suhardi, Suhardi (Magister Manajemen Universitas Wisnuwardhana, 2025)
This research aims to determine the influence of supervision, work discipline and motivation on employee performance at PT Microcast Technology Indonesia. The population in the study were employees of PT Microcast Technology Indonesia. The sample in this research was 100 employees or all employees of PT Microcast Technology Indonesia. This research uses quantitative methods, data analysis uses the SPSS 26 program. The results of this research show that, Supervision has a positive and significant effect on Employee Performance at PT Microcast Tecnology Indonesia , work discipline has a positive and significant effect on Employee Performance at PT Microcast Tecnology Indonesia and Motivation has an effect positive and significant impact on Employee Performance at PT Microcast Tecnology Indonesia, as well as Supervision, Work Discipline and Motivation simultaneously have a positive and significant impact on Employee Performance at PT Microcast Tecnology Indonesia.